STUDY OF GROWTH PROMOTING EFFECTS OF AYU-707 - A POLYHERBAL POWDER IN IMMATURE RATS - Manandhar, Suman; N, Chaitra; Kumar Be, Vinay; Kc, Thriveni; Kp, Shivalinge Gowda (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The growth promoting effects of AYU-707 was investigated in 1 and 2 months immature rats. Methods: The AYU-707 was administered orally at a dose of 5 (1-month-old rats) and 6.5 g/kg body weight (BW) (2-month-old rats) for 45 days. During and end of the study, BW, tail length, body circumference, and feed efficiency were determined. After 24 hrs of the last treatment, the blood was withdrawn by retro-orbital puncture and blood, hemoglobin, serum alkaline phosphatase, serum glutamate-oxaloacetate transaminase, serum glutamic-pyruvic transaminase, calcium, total protein, and amylase were estimated. Then, the rats were sacrificed by overdose ketamine and the femur weight, tibial density, bone hydroxyproline content, and epiphyseal plate width were determined. Then, the spleen, lung, liver, kidney, heart, and uterus weights were determined. Results: The preliminary phytochemical investigation confirms the presence of carbohydrate, amino acid, alkaloids, flavonoids, and tannins in AYU707 powder. The rats treated with AYU-707 have shown significant differences in most of the growth enhancement parameters when compared to the normal rats. Conclusion: From the results of the present study, it is concluded that AYU-707 formulated by M/s Ayurwin Pharma Pvt. Ltd., Bengaluru, possesses superior anabolic and growth promotion properties that may serve to promote the growth in children associated with growth-related disorders. Keywords: Body circumference, Tibial density, Flavonoids, Hydroxyproline, Epiphyseal plate.